Molded article containing side-chain crystalline block copolymer and method for producing same
By melting thermoplastic resin with a side chain crystalline block copolymer, the method addresses the limitations of solvent-based surface modification, achieving enhanced surface properties and maintaining inner layer integrity in molded bodies.
Patent Information
- Application Number
- JP2020100915
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-10
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2040-06-10
AI Technical Summary
Existing methods for modifying thermoplastic resin surfaces using side chain crystalline block copolymers require solvents, limiting manufacturing flexibility and surface modification to only the outer layer, and can lead to undesirable changes in the inner layer properties.
A method for manufacturing a molded body by melting a thermoplastic resin with a side chain crystalline block copolymer, allowing for selective uneven distribution of the copolymer on the surface layer without using solvents, ensuring the inner layer properties remain unchanged.
The method enables the formation of a modified surface layer with enhanced properties such as adhesion and metal adsorption, while maintaining the integrity of the inner layer, offering greater manufacturing flexibility and improved surface modification efficiency.
Smart Images

Figure 0007625239000012 
Figure 0007625239000013 
Figure 0007625239000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a molded article containing a side-chain crystalline block copolymer, and a method for producing the same. [Background technology]
[0002] Many thermoplastic resins, such as polyolefin resins, have been molded for various applications and put to practical use. The physical properties of molded bodies of these resins differ depending on the nature of each resin. These molded bodies may be required to have specific physical properties such as adhesiveness on the surface. To modify the surface of molded bodies of these resins, plasma treatment, corona treatment, flame treatment, UV irradiation, etc. have been used to impart adhesiveness to the surface. However, such treatments require special equipment, and the effect may be limited to a short period of time.
[0003] As a method for modifying such resin moldings, the present inventors have proposed a method using a side-chain crystalline block copolymer (SCCBC) having a block with a long alkane chain in the side chain and a functional block that exhibits various functionalities (Patent Documents 1 to 3, Non-Patent Document 1).
[0004] For example, Patent Document 1 relates to a surface modification material comprising a substrate at least a part of which is polyethylene and a polymer that modifies the surface of the polyethylene, the polymer being a block copolymer of monomers including a first monomer that is an acrylate having an alkane chain having 10 or more carbon atoms and a second monomer that is an acrylate of a tertiary amine, or a block copolymer of monomers including a first monomer that is a (meth)acrylate having an alkane chain having 10 or more carbon atoms and a second monomer that is a (meth)acrylate having a side chain having 4 or more carbon atoms and a -CF2- structure. Specifically, a method of modifying the surface of a substrate with a surface modification composition is disclosed, for example, in which the surface modification composition is attached to the surface of the substrate by a dipping method or a coating method, and then the dispersion medium is removed.
[0005] Patent Document 2 discloses a method for modifying a polyethylene resin molded product, comprising the steps of: preparing a copolymer solution by dissolving in a solvent a copolymer for modifying polyethylene, the copolymer having a structure derived from a first monomer (A) and a structure derived from a second monomer (B), the monomer (A) being a monomer having an alkane chain with a length of 8 carbon atoms or more in its side chain, and the monomer (B) being a monomer having a specific fluorinated alkyl group in its side chain; bringing the copolymer solution into contact with a polyethylene resin molded product; and forming the copolymer layer on the surface of the molded product by volatilizing the solvent of the copolymer solution brought into contact with the molded product.
[0006] Patent Document 3 discloses a method for modifying a polypropylene resin molded body, comprising the step of contacting a copolymer solution containing a side-chain crystalline block copolymer with a polypropylene resin molded body at a temperature of the copolymer solution of 40 to 120°C. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6445258 [Patent Document 2] JP 2018-030927 A [Patent Document 3] JP 2019-137779 A [Non-patent literature]
[0008] [Non-Patent Document 1] Journal of Adhesion Science and Technology, 2019, 33, 2567-2578. Summary of the Invention [Problem to be solved by the invention]
[0009] Patent Documents 1 to 3 disclose methods using a solution or dispersion in which a side-chain crystalline block copolymer is dissolved or dispersed in a solvent. These methods can modify a resin molded body, but require coating or immersion in a solvent.
[0010] When using a solvent, a coating or immersion process is required, and a drying process is also required, but there may be environments or products where the use of solvents is restricted. In addition, only the surface that can come into contact with the solution or dispersion liquid is modified. In order to improve the flexibility of manufacturing conditions, new methods that can obtain modified molded bodies are also required.
[0011] Under such circumstances, an object of the present invention is to provide a molded article having a modified surface layer or a layer near the surface, and a method for producing the same. [Means for solving the problem]
[0012] As a result of intensive research aimed at solving the above problems, the present inventors have found that the following invention meets the above object, and have completed the present invention.
[0013] <1> A method for producing a molded article, comprising melt molding a kneaded resin obtained by kneading a thermoplastic resin and a side-chain crystalline block copolymer, thereby modifying a surface layer of the molded article. <2> the thermoplastic resin is one or more resins selected from the group consisting of polyolefin-based resins, polyester-based resins, polystyrene-based resins, and polyacrylic-based resins; The content of the side chain crystalline block copolymer in the kneaded resin (mass of the side chain crystalline block copolymer / mass of the kneaded resin) is 0.05 to 10.0% by mass. <1> A method for producing the molded article according to claim 1. <3> The side chain crystalline block copolymer includes a first polymer block which is a repeat of a structural unit having an alkyl group having 8 or more carbon atoms in a side chain, and a second polymer block which is a repeat of a structural unit having a functional group. <1> or <2> A method for producing the molded article according to claim 1. <4> The functional group is a polar group and / or a functional group having a metal adsorption ability. <3> A method for producing the molded article according to claim 1. <5> the first polymer block is a polymer of any one monomer (A) selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, the monomer having an alkyl group having 8 or more carbon atoms; the second block being a polymer of any one of monomers (B) having any one group selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, the monomer (B) having any one group selected from the group consisting of an amino group, an amide group, a sulfo group, an oxyalkylene group, and an oxiranyl group; <3> or <4> A method for producing the molded article according to claim 1. <6> The composition contains a thermoplastic resin and a side-chain crystalline block copolymer, a surface layer having a portion where the side chain crystalline block copolymer is selectively distributed and arranged; a surface-nearby layer in contact with the surface layer and having a portion containing the side-chain crystalline block copolymer. Effect of the Invention
[0014] According to the manufacturing method of the present invention, a molded article having a modified surface layer can be obtained. In addition, the molded article of the present invention has a surface layer or a layer near the surface that contains a side-chain crystalline block copolymer and has modified physical properties. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a diagram showing an example of a molding apparatus used for producing a raw material for the molded body of the present invention. [Diagram 2] FIG. 2 is a diagram showing another example of a molding apparatus used for producing a molded article of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The following is a detailed description of the embodiments of the present invention, but the following description of the constituent elements is one example (representative example) of the embodiment of the present invention, and the present invention is not limited to the following content as long as the gist of the present invention is not changed. Note that in this specification, when the expression "~" is used, it is used as an expression including the numerical values before and after it.
[0017] [Method of manufacturing the molded article of the present invention] The method for producing a molded article of the present invention is a method for producing a molded article in which a kneaded resin obtained by kneading a thermoplastic resin and a side-chain crystalline block copolymer is melt-molded to modify the surface layer of the molded article. According to the method for producing a molded article of the present invention, a molded article having a modified surface layer can be obtained. This production method does not require treatment with a solvent or the like, and can produce a molded article having a modified surface layer molded into any shape.
[0018] [Molded article of the present invention] The molded article of the present invention has a surface layer that contains a thermoplastic resin and a side-chain crystalline block copolymer and has a portion where the side-chain crystalline block copolymer is selectively distributed and arranged unevenly, and a surface-nearby layer that is in contact with the surface layer and has a portion containing the side-chain crystalline block copolymer.
[0019] The molded article of the present invention can be produced by the method for producing a molded article of the present invention, and the corresponding configurations in the present application can be used interchangeably.
[0020] The present inventors have investigated the use of side-chain crystalline block copolymers to modify the surface layer or the layer near the surface of a thermoplastic resin. Thermoplastic resins are melt-molded by injection molding, extrusion molding, etc. The thermal history during this melt molding is a high-temperature process, and it is necessary to take into consideration the heat resistance and behavior during heating, and it is thought that there are limitations to what can be mixed.
[0021] When modifying various molded products using side chain crystalline block copolymers, they have been used in a dissolved or dispersed state in a solvent. The amount of side chain crystalline block copolymer used in this case is relatively small because it is directly applied to the surface. However, when used in molding involving melt kneading of a thermoplastic resin composition, it may be necessary to use a considerably large amount, taking into consideration the amount that is uniformly dispersed and remains on the surface. On the other hand, there is a concern that micellization, in which the side chain crystalline block copolymers self-aggregate, may occur when a large amount of side chain crystalline block copolymer is mixed. When micellization occurs, the physical properties that are mainly contributed by the inner layer of the molded product may change significantly, making it unsuitable for the initial use or making it impossible to obtain a molded product.
[0022] Assuming such a situation, the present inventors mixed a relatively small amount of a side-chain crystalline block copolymer into a thermoplastic resin and performed melt molding. As a result, they found that the side-chain crystalline block copolymer can be selectively distributed in the surface layer or the layer near the surface, and the effect on the inner layer is small, and the surface layer or the layer near the surface can be modified. In addition, at this time, the side-chain crystalline block copolymer does not completely precipitate on the surface, and a part of the structure has a high affinity with the thermoplastic resin, so it is considered that a phenomenon like anchoring occurs in which the side-chain crystalline block copolymer is arranged toward the inner layer of the molded body, and a stable modification effect is achieved. The present invention is based on such findings.
[0023] [Thermoplastic resin] The molded article in the present invention is a molded article of a resin composition containing a thermoplastic resin as a main component. The thermoplastic resin is a resin that exhibits plasticity when heated. The thermoplastic resin may be any resin that is molded into a state having fluidity by heating, such as injection molding or extrusion molding. The resin composition is a composition that contains such a thermoplastic resin as a main component.
[0024] The resin composition may contain 50% by mass or more of the thermoplastic resin. Depending on the type of thermoplastic resin, the use of the molded article, other mixtures, etc., the proportion of the thermoplastic resin in the resin composition may be 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more.
[0025] The resin composition contains at least a side-chain crystalline block copolymer as a component other than the thermoplastic resin. In addition to these, the resin composition may contain various components contained in a molded article using the resin composition.
[0026] The thermoplastic resin may be, for example, a polyolefin resin, a polyester resin, a polystyrene resin, or a polyacrylic resin. In particular, the thermoplastic resin is preferably hydrophobic. The thermoplastic resin may include a plurality of types of resins.
[0027] The thermoplastic resin is particularly preferably a polyolefin resin. A polyolefin resin is a crystalline polymer obtained by polymerization of an α-olefin having a double bond at the 1-position, such as a polyethylene resin or a polypropylene resin. Examples of polyolefin resins include polyethylene resins and polypropylene resins. Resins containing polyethylene as the main component may be called polyethylene resins, and those containing polypropylene as the main component may be called polypropylene resins.
[0028] In addition, recycled resins may be used as these thermoplastic resins. The recycled resin is a general term for pre-consumer products such as waste and defective products generated in the process of molding a thermoplastic resin composition from virgin pellets, and resins that are distributed on the market as molded bodies such as recycled plastic containers and packaging (so-called "container replastics") and are discarded after consumption. An example of such a recycled resin is a recycled polyolefin resin, such as a polyethylene resin or polypropylene resin manufactured (regenerated) from container and packaging plastics.
[0029] Polyester resins are polycondensates synthesized by dehydrating and condensing polycarboxylic acids and polyhydric alcohols to form ester bonds. Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polycyclohexane dimethylene terephthalate, and polyethylene naphthalate (PEN).
[0030] A polystyrene-based resin is a polymer obtained by polymerizing a styrene derivative as a monomer.
[0031] Polyacrylic resins are polymers that are polymerized using acrylic acid esters or methacrylic acid esters as monomers, such as PMMA (polymethyl methacrylate).
[0032] [Side chain crystalline block copolymer] A side-chain crystalline block copolymer is a block copolymer of a polymer having a structure exhibiting crystallinity in the side chain and a polymer having a structure exhibiting a modifying effect, and is a copolymer that can form a site in a thermoplastic resin where a part of this block copolymer interpenetrates.
[0033] The side-chain crystalline block copolymer includes a first polymerization block which is a repeating unit having an alkyl group (alkane chain) having 8 or more carbon atoms in the side chain, and a second polymerization block which is a repeating unit having a functional group. The first polymerization block can be a polymerized monomer (A), and the second polymerization block can be a polymerized monomer (B), and the copolymers thereof can be used.
[0034] The monomer (A) is preferably any monomer selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, which has an alkane chain having 8 or more carbon atoms in its side chain, and the monomer (B) is preferably a monomer having a functional group. In addition, it may be a block copolymer having a polymerization block derived from monomer (A), which is a portion formed by polymerization of monomer (A), and a polymerization block derived from monomer (B), which is a portion formed by polymerization of monomer (B).
[0035] In a side-chain crystalline block copolymer, the structure derived from monomer (A) is sometimes called "block (A)" and the structure derived from monomer (B) is sometimes called "block (B)."
[0036] The side chain crystalline block copolymer used in the present application may be one that references the side chain crystalline block copolymers disclosed in Japanese Patent No. 6445258, JP 2018-030927 A, JP 2019-137779 A, JP 2018-080329 A, etc.
[0037] [Monomer (A)] The monomer (A) is preferably any monomer selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, which has an alkane chain with a length of 8 or more carbon atoms in the side chain. By using this monomer (A), the side chain crystalline block copolymer has a constituent unit (A) derived from the monomer (A).
[0038] In the present application, the term "(meth)acrylate" refers to both acrylate and methacrylate. Similarly, the term "(meth)acrylamide" refers to both acrylamide and methacrylamide.
[0039] Unit The structural unit (A) is preferably a structural unit derived from a (meth)acrylate or α-olefin monomer having an alkane chain in its side chain with a length of 8 or more carbon atoms, since the alkane chain in the side chain is likely to have a crystalline structure and is likely to interact with the thermoplastic resin.
[0040] The structural unit (A) has an alkane chain having 8 or more carbon atoms in its side chain. Examples of the alkane chain having 8 or more carbon atoms in the side chain of the structural unit (A) include a decyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a hexadecyl group, an octadecyl group (stearyl group), a docosyl group (behenyl group), and the like. The alkane chain in the side chain may be directly bonded to the main chain, or may be bonded to the main chain via a linking group such as an ester bond, an amide bond, an ether bond, or a benzene ring.
[0041] Since the structural unit (A) is likely to exhibit crystallinity and can further improve the interaction between the copolymer and the thermoplastic resin, it is preferable that the structural unit (A) has an alkane chain having 12 or more carbon atoms, and more preferably has an alkane chain having 16 or more carbon atoms. The alkane chain is preferably a linear alkane chain.
[0042] On the other hand, the upper limit can be appropriately set within a range that can modify the surface of the thermoplastic resin, taking into consideration dispersibility in the solvent during production and dispersibility during melt molding. A specific upper limit is preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less in reality. If the alkane chain is too large, the copolymer may not have a proper three-dimensional structure, and the interpenetration with the thermoplastic resin may decrease. In addition, it may be difficult to set the polymerization conditions for producing a side-chain crystalline block copolymer.
[0043] Specifically, the block (A) is preferably any one of those represented by the following general formula (A-1) or (A-2).
[0044] [ka]
[0045] In the general formulas (A-1) and (A-2), R a1 represents a hydrogen atom or a methyl group.
[0046] In the general formulas (A-1) and (A-2), R a2 represents an alkane chain having 8 or more carbon atoms. As mentioned above, R a2 is preferably a linear alkane chain. a2 The number of carbon atoms in the alkane chain represented by the formula (I) is preferably 12 or more, and more preferably 16 or more. The upper limit can be 50 or less, 40 or less, 30 or less, 25 or less, or the like.
[0047] From the viewpoints of ease of obtaining monomers, ease of controlling polymerization conditions, ease of interaction between alkane chains having 8 or more carbon atoms, etc., the block (A) is more preferably a block of the general formula (A-1).
[0048] In the general formulas (A-1) and (A-2), n is an integer of 2 or more. n is appropriately determined within a range in which the surface layer of a molded thermoplastic resin can be modified depending on the length of the alkane chain of the side chain, the arrangement of the structural unit (A) and the structural unit (B), the polymerization degree of the structural unit (B), etc. When the side chain crystalline block copolymer is a block copolymer, n is preferably 2 to 1,000, and more preferably 5 or more or 10 or more. By making it 5 or more or 10 or more, the side chain is likely to have crystallinity, and it is possible to more stably melt-knead with the thermoplastic resin to modify the surface layer of the molded body. In addition, when the side chain crystalline block copolymer is a block copolymer, n may be 800 or less or 500 or less within a range in which the effects of the structural unit (A) and the structural unit (B) can be sufficiently obtained.
[0049] Specific examples of monomer (A) include hexadecyl acrylate, dodecyl acrylate (lauryl acrylate), dodecyl methacrylate (lauryl methacrylate), octadecyl acrylate (stearyl acrylate), octadecyl methacrylate (stearyl methacrylate), docosyl acrylate (behenyl acrylate), docosyl methacrylate (behenyl methacrylate), and the like.
[0050] [Monomer (B)] The monomer (B) is a monomer having a functional group. The functional group may have a polar group.
[0051] The monomer (B) may be any monomer selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, having any one selected from the group consisting of an amino group, an amide group, a sulfo group, an oxyalkylene group, and an oxiranyl group.
[0052] [Block] The side chain crystalline block copolymer may have a structural unit (B) having a structure having a functional group in the side chain.
[0053] [Functional group] Here, the functional group is a group that exists in the copolymer after polymerization and that has a function of modifying the molded article of the present invention. Examples of functionality include hydrophilicity, ion conductivity, adhesiveness, heavy metal carrying ability, affinity for organic solvents, and dyeability. The functional group has a structure corresponding to these. Representative polar groups include an amino group (-NR2), a carboxy group (-COOH), a hydroxy group (-OH), a carbonyl group (-C=O-), an ether group (-O-), a sulfo group (-SO3H), an ester group (-COO-), an amide group (-CONR2-), an oxyalkylene group (-C n H 2n These functional groups are bonded directly to the main chain or to a portion that becomes the main chain of (B), or bonded via a linking group (an ester bond, an amide bond, an ether bond, a benzene ring, etc.).
[0054] [Polar group] The side chain crystalline block copolymer may have a structural unit (B) having a structure with a polar group in the side chain. Here, the polar group is a group with a large bias in the charge distribution. By using a copolymer having a structure with these polar groups, the modified molded body has the effects of improving adhesion, hydrophilicity, dyeability, etc.
[0055] [Metal adsorption capacity] The side chain crystalline block copolymer may have a structural unit (B) having a structure exhibiting metal adsorption ability in the side chain. Here, the metal adsorption ability means that a molecular structure that exhibits adsorption properties with metals or metal ions due to the presence of a polar group in the molecular structure, or that is easily chemically bonded to or forms a complex with metals or metal ions, is provided in the copolymer, and the structure is arranged on the surface of a molded article, thereby exhibiting the property of supporting, adsorbing, and retaining metals or metal ions.
[0056] [Group of structural unit (B)] The structural unit (B) preferably has at least one group selected from the group consisting of an amino group, an amido group, a sulfo group, an oxyalkylene group, and an oxiranyl group.
[0057] More preferred are structures derived from any monomer selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene having these structures in the side chain.
[0058] [Amino group] Monomer (B) may have an amino group. This amino group exists as an amine in the structure of the side chain crystalline block copolymer after polymerization. Here, amine is a general term for a compound in which a hydrogen atom of ammonia is substituted with a hydrocarbon group. A compound with one substitution is called a primary amine, a compound with two substitutions is called a secondary amine, a compound with three substitutions is called a tertiary amine, and a compound in which an alkyl group is bonded to a tertiary amine is called a quaternary ammonium ion. These various amines exist in the side chain crystalline block copolymer as a structure derived from monomer (B), and thus functions such as hydrophilicity, ion conductivity, adhesiveness, dyeability, metal adsorption ability, heavy metal support, and organic solvent affinity can be exhibited. In addition, by using a copolymer having such various amines, excellent plating adhesion to a molded body can be exhibited. When used for plating, etc., it is particularly preferable to use a monomer having a tertiary amine.
[0059] Specific examples of the monomer (B) include any monomer having a secondary or tertiary amine and selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene. The amine of this monomer becomes a side chain of the copolymer, and it exhibits hydrophilicity, ion conductivity, adhesiveness, dyeability, metal adsorption ability, heavy metal carrying ability, organic solvent affinity, etc. Furthermore, any one selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene forms the main chain of the copolymer.
[0060] In particular, in order to exert these functions, it is preferable to use a monomer having a secondary, tertiary, or quaternary amine in the side chain of the monomer (B). More specifically, the secondary and tertiary amines are substituents having a structure represented by "-N(R1)(R2)", where R1 and R2 are each independently H or a hydrocarbon. The number of carbon atoms in the hydrocarbon can be, for example, 1 to 4.
[0061] The structure derived from the monomer (B) is a structure of a side chain crystalline block copolymer as the block (B). The structural unit (B) derived from the monomer (B) may have an amino group in the side chain, and thus may have an amine structure in the side chain. For example, the structural unit (B) may have a substituent represented by the general formula (Y) in the side chain. The general formula (Y) may be directly bonded to the main chain, or may be bonded to the main chain via a linking group such as an ester bond, an amide bond, an ether bond, a benzene ring, or an alkylene chain (alkylene group). The alkylene chain may have about 1 to 5 carbon atoms or about 1 to 3 carbon atoms.
[0062] [ka]
[0063] In the general formula (Y), R y1 , R y2are each independently a hydrogen atom, an alkyl group, or a carboxyalkylene group. A carboxyalkylene group is a substituent in which a carboxy group and an alkylene group are bonded, and the alkylene group is represented by R alkylene Expressed as -R alkylene It is a substituent represented by -COOH. Among them, R y1 and R y2 R is preferably a hydrogen atom, a linear or branched alkyl group having 1 to 5 carbon atoms, or a carboxyalkylene group having 1 to 5 carbon atoms. The number of carbon atoms in the alkyl group or carboxyalkylene group may be 1 to 4. y1 and R y2 When the number of carbon atoms in the alkyl group or alkylene group represented by the formula (I) is large, it may become difficult to interact with the metal.
[0064] In addition, it is possible to use those in which these substituents are appropriately bonded to any of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene via an alkylene chain having about 1 to 5 carbon atoms or about 1 to 3 carbon atoms. For example, 2-(dimethylamino)ethyl methacrylate (DMAEMA), 2-(dimethylamino)ethyl acrylate (DMAEA), 2-(diethylamino)ethyl methacrylate (DEAEMA), 2-(diethylamino)ethyl acrylate (DEAEA), and 2-(tert-butylamino)ethyl methacrylate (TBAEMA) can be mentioned.
[0065] [Amide group] The monomer (B) may have an amide group. A monomer in which the amide group is bonded to the main chain structure via an alkylene chain having about 1 to 5 carbon atoms or 1 to 3 carbon atoms, or directly, can be used. A copolymer using this monomer can impart hydrophilicity, ion conductivity, adhesiveness, dyeability, metal adsorption ability, heavy metal supportability, organic solvent affinity, etc. to a molded thermoplastic resin. Specific examples of monomers having an amide group in a side chain include N,N-dimethylacrylamide (DMAA), N,N-dimethylaminopropyl acrylamide (DMAPAA), and N,N-diethylacrylamide (DEAA).
[0066] [Sulfo group] The monomer (B) may have a sulfo group. In addition, a monomer in which the sulfo group is appropriately bonded to the main chain structure via an alkylene chain having about 1 to 5 carbon atoms or 1 to 3 carbon atoms, or directly, can be used. A copolymer using this monomer can impart hydrophilicity, proton conductivity, ion conductivity, adhesiveness, dyeability, metal adsorption ability, heavy metal supportability, organic solvent affinity, etc. to a molded body of a thermoplastic resin. Examples of the monomer having a sulfo group include vinyl sulfonic acid, 2-(methacryloyloxy)ethanesulfonic acid, ATBS (Acrylamide Tertiary Butyl Sulfonic Acid), and its sodium salt ATBSNa.
[0067] [Oxyalkylene group] The monomer (B) may have an oxyalkylene group. Here, the oxyalkylene group is represented by the general formula (-C n H 2nIn this general formula, n is preferably an integer of 1 to 10. For example, when n is 1, it is called oxymethylene (-CH2O-), and when n is 2, it is called oxyethylene (-CH2CH2O-). A plurality of these oxyalkylene groups are linked together to form a polyoxyalkylene group (general formula: (-C n H 2n O) m -) is called a typical linear polyoxyalkylene group ((-(CH2) n O) m -) is polyoxyethylene ((-CH2CH2O) m By using a monomer having these oxyalkylene groups or polyoxyalkylene groups as the main chain or side chain as the monomer (B) to prepare a copolymer, it is possible to impart hydrophilicity, ion conductivity such as Li, adhesiveness, dyeability, metal adsorption ability, heavy metal support ability, organic solvent affinity, etc. to a molded product of a thermoplastic resin.
[0068] The monomer (B) having an oxyalkylene group may be any monomer selected from the group consisting of (meth)acrylates, (meth)acrylamides, vinyl ethers, vinyl esters, siloxanes, α-olefins, and substituted styrenes having an oxyalkylene group in the side chain. A copolymer using this monomer can impart hydrophilicity, ion conductivity, adhesiveness, dyeability, metal adsorption ability, heavy metal support, organic solvent affinity, etc. to a thermoplastic resin molded article. In addition, the use of such a copolymer can provide excellent plating adhesion to the resin molded article.
[0069] The structural unit (B) having an oxyalkylene group on the side chain can be, for example, one having a substituent represented by general formula (X) on the side chain. In addition, general formula (X) may be directly bonded to the main chain, or may be bonded to the main chain via a linking group such as an ester bond, an amide bond, an ether bond, a benzene ring, or an alkylene chain.
[0070] [ka]
[0071] In the general formula (X), R x1 is a hydrogen atom or an alkyl group, p is an integer of 1 or more, and q is an integer of 1 or more. R x1 The alkyl group represented by may be linear or branched, but is preferably linear. If the number of carbon atoms in the alkyl group is large, the interaction with the molded body of the thermoplastic resin becomes strong, and the metal adsorption ability may not be fully exhibited, or the interaction with the metal catalyst may become difficult. For this reason, x1 is preferably a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and more preferably a hydrogen atom, a methyl group, or an ethyl group.
[0072] p is preferably 1 to 10. In addition, q is preferably 2 to 10 because it facilitates interaction with metals due to the chelating effect.
[0073] Monomers having an oxyalkylene group include di(ethylene glycol) ethyl ether acrylate (CH2=CH(CO)O(CH2-CH2-O-)2C2H5), polyethylene glycol monoacrylate (CH2=CH(CO)O(CH2-CH2-O-) n H) (n = 2-10), methoxy-polyethylene glycol-acrylate (CH2=CH(CO)O(CH2-CH2-O-) n CH3) (n=2 to 9), etc. Also included are monomers having a polyoxyalkylene structure in the side chain, such as poly(ethylene glycol) monoacrylate (PGMA).
[0074] [Oxiranyl group] The monomer (B) may be any monomer selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene having an oxiranyl group. Examples of the monomer (B) include glycidyl acrylate and glycidyl methacrylate.
[0075] The copolymer obtained by using these monomers has an oxiranyl group in the side chain. When the oxiranyl group in the side chain is reacted with a compound having a tertiary amine such as iminodiacetic acid as a reactive group, the copolymer has a tertiary amine structure derived from iminodiacetic acid in the side chain, and exhibits metal adsorption ability.
[0076] [Chelate structure] The structural unit (B) can have a chelate structure in the side chain. The structure having a chelate structure can have various structures such as an iminodiacetic acid (IDA) group, a low molecular weight polyamino group, an aminophosphate group, an isothionium group, a dithiocarbamic acid group, a glucamine group, and an oxyalkylene structure.
[0077] [General formula (B-1)~(B-4)] Specifically, examples of the block (B) include structures represented by the following general formulas (B-1) to (B-4), which are structures having (meth)acrylate, (meth)acrylamide, vinyl ether, and vinyl ester, respectively.
[0078] [ka]
[0079] In general formulae (B-1) to (B-4), R b1 represents a hydrogen atom or a methyl group. L represents a single bond or an alkylene chain, and is preferably a single bond or an alkylene chain having 1 to 4 carbon atoms. The alkylene chain may have a substituent such as an alkoxy group, a hydroxy group, or a hydroxyalkyl group.b2 An unsubstituted alkylene chain is preferred because it increases the degree of freedom of the alkylene chain and makes it easier to assume a configuration that easily interacts with metals, thereby improving affinity with metals.
[0080] In general formulae (B-1) to (B-4), R b2 represents any one selected from the group consisting of a hydrogen atom, an alkylene chain, a hydroxyl group, an amino group, a sulfo group, an oxiranyl group, and a substituent represented by general formula (X). The substituent represented by general formula (X) is as described above. It easily interacts with metals and provides better adhesion to the plating layer, making it a highly effective b2 is preferably an amino group or a substituent represented by the general formula (X). The amino group may be an unsubstituted amino group (-NH2) or an amino group substituted with an alkyl group or the like, but is more preferably a structure represented by the general formula (Y).
[0081] In general formula (B-2), R b3 represents a hydrogen atom or an alkyl group, preferably a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and more preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms.
[0082] [General formula (B-5)~(B-7)] Moreover, the block (B) can have structures of the following general formulas (B-5) to (B-7), which are structures having siloxane, α-olefin, and substituted styrene, respectively.
[0083] [ka]
[0084] In general formulae (B-5) to (B-7), R b1 represents a hydrogen atom or a methyl group. Lrepresents a single bond or an alkylene chain, and is preferably a single bond or an alkylene chain having 1 to 4 carbon atoms. The alkylene chain may have a substituent such as an alkoxy group, a hydroxy group, or a hydroxyalkyl group, but is preferably an unsubstituted alkylene chain.
[0085] R b4 represents any one selected from the group consisting of a hydroxy group, an amino group, a sulfo group, an oxiranyl group, and a substituent represented by general formula (X). The substituent represented by general formula (X) is as described above.
[0086] For example, when used for plating, it easily interacts with metals and provides better adhesion to plating, making it a good choice for R b4 is preferably an amino group or a substituent represented by the general formula (X). The amino group may be an unsubstituted amino group (-NH2) or an amino group substituted with an alkyl group or the like, but is more preferably a structure represented by the general formula (Y).
[0087] In the general formulas (B-1) to (B-7), m is an integer of 2 or more. m is appropriately determined depending on the structure of the group having metal adsorption ability, the arrangement of the structural unit (A) and the structural unit (B), the degree of polymerization of the structural unit (B), etc.
[0088] In the side chain crystalline block copolymer, m is preferably 2 to 1,000. In order to exert a more stable modifying effect and impart metal adsorption ability to the surface of a molded thermoplastic resin article, m is preferably 2 or more, and more preferably 5 or more or 10 or more. Moreover, m may be set to 800 or less, or 500 or less, as long as the effects of the structural unit (A) and the structural unit (B) can be sufficiently obtained.
[0089] [Copolymer] The side chain crystalline block copolymer is a copolymer containing a structural unit (A) and a structural unit (B). The side chain crystalline block copolymer may further contain other structural units within a range that does not impair the object of the present invention. For example, as described below, when the structural unit (B) is obtained by introducing a metal-adsorbing site into the side chain of its precursor polymer, the side chain crystalline block copolymer may contain a structure derived from the precursor monomer of the structural unit (B) in addition to the copolymer (A) and the copolymer (B).
[0090] The side chain crystalline block copolymer contains the structural unit (A) and the structural unit (B) as main components, and the total proportion of the structural unit (A) and the structural unit (B) in the side chain crystalline block copolymer is preferably 80 mass% or more, and more preferably 90 mass% or more.
[0091] One of the preferred side chain crystalline block copolymers is a copolymer containing a block (A) represented by general formula (A-1) or (A-2) and a block (B) represented by general formula (B-1), and more preferably a copolymer containing a block (A) represented by general formula (A-1) and a block (B) represented by general formula (B-1).
[0092] The side chain crystalline block copolymer may be any of a random copolymer, an alternating copolymer, a block copolymer, a triblock copolymer, etc., but is preferably a block copolymer. By using the block copolymer, the functions of the structural unit consisting of the block (A) and the structural unit consisting of the block (B) can be easily and sufficiently exhibited.
[0093] In the side chain crystalline block copolymer, the molecular weight corresponding to the block (A) and the molecular weight corresponding to the block (B) are each preferably 1000 or more. When the molecular weight corresponding to the block (A) is 1000 or more, it is possible to more firmly adhere to a molded article of a thermoplastic resin serving as a substrate. The molecular weight corresponding to the block (A) is preferably 1,500 or more, and more preferably 2,000 or more.
[0094] Furthermore, a copolymer having superior metal adsorption ability can be obtained by having the molecular weight corresponding to block (B) of 1000 or more. The molecular weight corresponding to block (B) is preferably 1,500 or more, and more preferably 2,000 or more.
[0095] These molecular weights are the values (Mw: weight average molecular weight) that can be calculated in polystyrene equivalent from the results obtained by GPC. In some cases, the copolymer is difficult to dissolve in a solvent and the weight average molecular weight is difficult to measure. In such cases, the weight average molecular weights can be calculated by methods such as elemental analysis, IR, and NMR.
[0096] An example of a side-chain crystalline block copolymer is a polymer represented by the following chemical formula (I). This is a block copolymer obtained by polymerizing behenyl acrylate (BHA: the side chain is a linear alkyl group having 22 carbon atoms) as the monomer (A) and then copolymerizing it with 2-(tert-butylamino)ethyl methacrylate (TBAEMA) as the monomer (B). This is a so-called AB-type block copolymer. This copolymer has a block copolymer portion that exhibits adhesion to a thermoplastic resin molded body due to the BHA-derived structure, and on the other hand, the TBAEMA-derived amine structure can impart metal adsorption ability to a thermoplastic resin molded body (subject to be treated).
[0097] Examples of side-chain crystalline block copolymers include polymers of the formulas (II), (III), and (IV), which use stearyl acrylate (STA) as monomer (A) and TBAEMA, diethylene glycol monoethyl ether acrylate (DEEA), and acrylic acid (AA) as monomer (B).
[0098] [ka]
[0099] [ka]
[0100] [Polymerization method] The polymerization method of the side chain crystalline block copolymer is not particularly limited, and the polymerization can be performed by known techniques such as various living polymerization methods (radical, anionic, cationic). As the living radical polymerization method, the NMP method, the ATRP method, the RAFT method, etc. can be used. In addition, as described above, the side chain crystalline block copolymer is preferably a block copolymer, and is preferably produced to be a block copolymer.
[0101] For example, it can be obtained by polymerizing a monomer (A) having an alkane chain with 8 or more carbon atoms in its side chain, which is any one selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, with a monomer (B1) having a structure with metal adsorption ability in its side chain.
[0102] Specifically, a monomer (A) mixed solution preparation step is performed in which the monomer (A) mixed solution is prepared by mixing the monomer (A) with a polymerization solvent together with an initiator. Next, the monomer (A) mixed solution prepared in the mixed solution preparation step is subjected to a monomer (A) polymerization step based on the polymerization mechanism of the initiator, such as living radical polymerization, in a nitrogen atmosphere or the like, while appropriately stirring the monomer (A) mixed solution prepared in the mixed solution preparation step at an appropriate polymerization temperature (e.g., about 90 to 120°C) in a reactor, to obtain a monomer (A) block polymer.
[0103] Furthermore, a monomer (B1) having a structure with metal adsorption ability in the side chain (e.g., a (meth)acrylate having an amino group) is mixed into the solution in which this monomer (A) block polymer has been mixed, and a monomer (B1) polymerization step is carried out in which the monomer (B1) is further polymerized by radicals in the solution. This makes it possible to obtain a block copolymer having a block derived from the monomer (A) and a block derived from the monomer (B1). The order in which the monomer (A) and the monomer (B1) are polymerized can be changed depending on the type and weight average molecular weight of the monomers to be polymerized, the polymerization conditions for each, and the like.
[0104] [Use of precursor polymers] Alternatively, the monomer (A) can be polymerized with a monomer (B2) (a precursor monomer of the structural unit (B)) having a reactive group such as an oxiranyl group on its side chain to synthesize a precursor polymer, which can then be reacted with an amino group or the like to obtain the structural unit (B).
[0105] Specifically, similarly to the above, monomer (A) is mixed with an initiator in a polymerization solvent, and the mixture is stirred appropriately in a reactor at an appropriate polymerization temperature (e.g., about 90 to 120°C) to carry out a monomer (A) polymerization step based on the polymerization mechanism of the initiator, such as living radical polymerization, under a nitrogen atmosphere or the like, to obtain a monomer (A) block polymer.
[0106] A monomer (B2) having an oxiranyl group (e.g., a (meth)acrylate having an oxiranyl group) is mixed into the solution containing the monomer (A) block polymer, and a monomer (B2) polymerization step is performed in which the monomer (B2) is further polymerized by radicals in the solution. This results in a solution containing a mixture of a precursor polymer having a block derived from the monomer (A) and a block derived from the monomer (B2). Next, when the precursor polymer is reacted with iminodiacetic acid, the oxiranyl group reacts with the iminodiacetic acid to form an amine structure derived from the iminodiacetic acid, and a copolymer having metal adsorption ability in the side chain of the block derived from the monomer (B2) is formed.
[0107] When other structural units are contained, they may be polymerized as monomer (C) with monomer (A) and monomer (B).
[0108] The side chain crystalline block copolymer thus synthesized can be used in a concentrated or dried state in the form of a paste or powder by appropriately heating or spray drying.
[0109] In the method for producing a molded article of the present invention, a kneaded resin is melt-molded into a molded article, thereby modifying a surface layer or a layer near the surface of the molded article.
[0110] [Mixed resin] The kneaded resin containing the thermoplastic resin and the side chain crystalline block copolymer can be prepared by any method. The kneaded resin may be prepared by kneading the thermoplastic resin and the side chain crystalline block copolymer in advance in a melt kneader to form a mass, which is then crushed appropriately to obtain a master batch.
[0111] The master batch may have a higher concentration of the side chain crystalline block copolymer than that in the modified molded article, making it easier to handle the side chain crystalline block copolymer. For example, the concentration of the side chain crystalline block copolymer in the resin of the master batch may be 5 to 80 mass%, 10 to 80 mass%, 30 to 80 mass%, or 40 to 80 mass%, etc. Such a master batch and a thermoplastic resin may be mixed in a dry state to control the concentration of the side chain crystalline block copolymer when producing the molded article of the present invention.
[0112] Alternatively, the components may be mixed in a dry state so as to be dispersed, and then fed as a raw material into a hopper of a molding machine to be kneaded into a kneaded resin in a melt-kneading section of the molding machine. Alternatively, a mixture may be kneaded in advance with a pelletizer or the like to be pelletized, and the pellets may be used as a raw material for further molding.
[0113] [ratio] The content of the side chain crystalline block copolymer in the kneaded resin (mass of side chain crystalline block copolymer / mass of kneaded resin) is preferably 0.05 to 10.0 mass %. By keeping the content within this range, a molded article having a surface modification effect achieved by the side chain crystalline block copolymer can be efficiently obtained.
[0114] If the content of the side chain crystalline block copolymer in the kneaded resin exceeds 10.0% by mass, the surface modification effect of the molded product may be saturated. In addition, since the amount of the side chain crystalline block copolymer is large, self-aggregation into micelles may occur, and the side chain crystalline block copolymer may form lumps in the inner layer or may appear in a spotty form on the surface layer. The content of the side chain crystalline block copolymer in the kneaded resin is more preferably 7.0% by mass or less, and may be 6.0% by mass or less, 5.0% by mass or less, 4.0% by mass or less, 3.5% by mass or less, or 3.0% by mass or less.
[0115] If the content of the side chain crystalline block copolymer is less than 0.05% by mass, the modifying effect may not be obtained. This content is more preferably 0.08% by mass or more, and may be 0.10% by mass or more, 0.15% by mass or more, 0.2% by mass or more, or 0.3% by mass or more.
[0116] [Pellet molding machine 10] Fig. 1 shows an example of a pellet molding machine for forming pellets, and Fig. 2 shows an example of a film molding machine for forming a film. These molding machines are suitable for the production method of the present invention.
[0117] The pellet molding machine 10 in Fig. 1 has a supply port 11, a supply port 12, a melt-kneading section 2, a discharge section 3, and a pelletizer 4. The pellet molding machine 10 can melt a resin composition and mold it into pellets. The resulting pellets 61 are collected in a container 5 such as a flexible container bag. The pellet molding machine 10 will be described in more detail below.
[0118] [Supply inlets 11 and 12] The supply ports 11 and 12 are hopper-shaped supply ports. A thermoplastic resin composition in the form of a lump, powder, pellets, or the like is supplied from the top of the supply ports 11 and 12 and transferred to the melt kneading section 2. Different raw materials can be fed into the supply ports 11 and 12, respectively. For example, a thermoplastic resin can be fed into the supply port 11, and a side-chain crystalline block copolymer can be fed into the supply port 12.
[0119] [Melting and kneading section 2] The melt-kneading section 2 melts and kneads the thermoplastic resin composition supplied from the supply ports 11 and 12. The melt-kneading section 2 is heated to the melting temperature of the thermoplastic resin composition, and the thermoplastic resin composition is extruded by rotating a screw 22 connected to a cylinder 21 by a motor M. In addition, when passing between the pipe and the screw, a shear stress is applied to the thermoplastic resin composition, and the thermoplastic resin composition is kneaded.
[0120] [Discharge part 3] The discharge section 3 discharges the thermoplastic resin composition after melt kneading in the form of strands. The pelletizer 4 chops the thermoplastic resin composition in the form of strands discharged from the discharge section 3 into pellets. The molding machine of the present invention may pelletize the composition by hot cutting or underwater cutting, which chops the composition immediately after discharge from the discharge section, and the strands may also be in a short state. The molding machine of the present invention may be a molding machine having a chopping section that chops the thermoplastic resin composition discharged from such a discharge section into pellets.
[0121] The resin pellets obtained by pelletizing the thermoplastic resin composition with this pellet molding machine 10 can be used as a master batch, and can also be used as a raw material when producing a molded article.
[0122] [Molding temperature] The molding temperature of the molded article of the present invention may be a standard molding temperature for the thermoplastic resin that is the main component, and this temperature can be controlled by the setting temperature of the screw part of the injection molding machine, etc.
[0123] 2 is equipped with a T-die 51 for film formation after the discharge section 3, instead of the pelletizer 4 of the molding machine 10 in FIG. 1. Also, instead of the supply ports 11 and 12, only the supply port 1 is provided. The resin composition discharged from the T-die 51 is discharged onto a roller 52, and formed into a film 62 while being appropriately stretched by a stretching roller (not shown) or the like, and then taken up by a winding roller 53.
[0124] [Molded body] The molded article of the present invention contains a thermoplastic resin and a side-chain crystalline block copolymer. The shape of the molded article molded using these resin compositions is not particularly limited, and examples thereof include molded articles such as sheets, plates, threads, filaments, fibers, porous materials, various members, and structures.
[0125] The molded article of the present invention has an orientation layer in which the side-chain crystalline block copolymer is selectively distributed and arranged in the surface layer, and a dispersion layer containing the side-chain crystalline block copolymer in the surface vicinity layer in contact with the orientation layer. The side-chain crystalline block copolymer in these surface layers and the surface vicinity layer may be confirmed by identifying the presence or absence and the degree of the side-chain crystalline block copolymer in each part in the thickness direction by IR. Alternatively, when the surface is washed, it may be confirmed by maintaining a certain degree of the physical properties modified by the presence of the surface vicinity layer. The surface layer is a layer directly exposed to the outside of the molded article. The surface vicinity layer is a layer inside this surface layer and close to the surface layer. EXAMPLES
[0126] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.
[0127] [Evaluation items] [IR spectrum] The measurements were performed using a Perkin Elmer Fourier transform infrared spectrometer "Spectrum two (registered trademark)."
[0128] [Tensile shear test (adhesion)] A tensile shear test was conducted according to JIS K6850 (1999) to evaluate the adhesiveness. A cyanoacrylate adhesive (product name: Aron Alpha 201, manufactured by Toagosei Co., Ltd.) was used as the adhesive. The test equipment used was a small tabletop tester EZ-LX manufactured by SHIMADZU. The test piece was 25 mm wide and 100 mm long, with an adhesive length of 12.5 mm. Both ends of the test piece were held by the gripping members of the measuring device and pulled apart at a rate of 10 mm / min to measure the adhesive strength. The test was performed three times, and the average value of the maximum load over the entire measurement range was calculated (referred to as "Maximum load (breaking force N)" in the table).
[0129] [Raw materials] HDPE: Asahi Kasei Corporation "Suntech (registered trademark) F184" ·LDPE: Ube Maruzen Polyethylene Co., Ltd. "UBE Polyethylene F522N" · L-LDPE: Asahi Kasei Corporation "Yumerit (registered trademark) 3540N" PP: Prime Polymer Co., Ltd. "Prime Polypro (registered trademark) J137G" Block PP: Prime Polymer Co., Ltd. "Prime Polypro (registered trademark) B-150"
[0130] [Monomer (A)] Monomer (A-1-1): BHA behenyl acrylate was used. This monomer has an alkyl group with 22 carbon atoms in the side chain.
[0131] [Monomer (B)] Monomer (B-1-1): TBAEMA 2-(tert-butylamino)ethyl methacrylate (TBAEMA) was used. This monomer has a secondary amino group in the side chain and a methacrylate structure in the main chain.
[0132] [Polymerization initiator] BlocBuilder (registered trademark) MA (manufactured by Arkema) [Solvent] Butyl acetate
[0133] [1] Production of block copolymers (1-1) Preparation of block copolymer (BHA-TBAEMA) 5.0 parts by mass of butyl acetate and 5.0 parts by mass of behenyl acrylate (BHA) were placed in a separable flask, and the butyl acetate and BHA were mixed, then degassed and replaced with nitrogen. Under a nitrogen atmosphere, the mixture of butyl acetate and BHA was stirred to dissolve the BHA in the butyl acetate, and 0.38 parts by mass of an initiator (Blocbuilder MA) was added. Under a nitrogen atmosphere, the BHA was polymerized at 110°C for 24 hours to obtain a BHA polymer solution. To the BHA polymer solution, 5.0 parts by mass of 2-(tert-butylamino)ethyl methacrylate (TBAEMA) and 5.0 parts by mass of butyl acetate were added, and polymerization was further carried out under a nitrogen atmosphere at 110° C. for 24 hours. Methanol was added to reprecipitate and dry, yielding a block copolymer of BHA and TBAEMA (BHA-TBAEMA).
[0134] The structural formula of the obtained BHA-TBAEMA is shown below as general formula (I): The block copolymer (BHA-TBAEMA) obtained in (1-1) had Mw of 10,000.
[0135] [ka]
[0136] [Mixing conditions] The thermoplastic resin and the side chain crystalline block copolymer were weighed and mixed in a dry state. · Kneading machine: Using "Labo Plastomill 4C150" manufactured by Toyo Seiki Seisakusho, preliminary kneading was performed to create a master batch. PE (HDPE, LDPE, L-LDPE) was mixed at 180°C, 30 rpm, and 3 minutes. PP (block PP) was kneaded at 210°C, 30 rpm, and 3 minutes.
[0137] [Polyethylene (PE) film production conditions] Film-forming conditions (A): The lump-shaped kneaded composition obtained by preliminary kneading was placed in a spacer having a thickness of 500 μm using a press molding machine, and press-molded at a press temperature of 180°C, a press pressure of 25 MPa, and a heating time of 2 minutes to obtain a film-shaped molded product. Film-forming condition (B): The remainder of the film formed under the film-forming condition (A) after the adhesive test piece was taken was recovered and used as a kneaded composition to form a film in accordance with the film-forming condition (A). Film-forming conditions (C): The thermoplastic resin and the side-chain crystalline block copolymer were weighed out and mixed in a dry state. The mixture was placed in a spacer of 500 μm in thickness using a press molding machine and pressed at 180°C to melt-knead and mold the mixture in the spacer of the press molding machine, obtaining a film-like molded product.
[0138] [Polyethylene (PP) film production conditions] The film was formed under the same conditions as above except that the press temperature of the polyethylene film was changed from 180°C to 210°C.
[0139] Tables 1 to 3 show the conditions and evaluation results of test examples in which film formation conditions, such as the type and concentration of thermoplastic resin and side chain crystalline block copolymer (SCCBC), were changed.
[0140] [Test Examples A1 to A14 and Comparative Example 1 (Table 1)] Table 1 relates to tests using HDPE. When HDPE was used, improved adhesive strength was observed at 0.1wt% or more in re-pressing (film-making condition (B)) and kneading (film-making condition (A)). On the other hand, a decrease in adhesive strength was observed at 5wt% or more. At 5wt%, adhesive strength improved by re-pressing, but at 10wt%, the adhesive strength modification effect was low even after re-pressing.
[0141] [Table 1]
[0142] [About Test Examples B1 to B14 (Table 2)] Table 2 shows the results of the test using PP. When PP was used, the adhesive strength was improved when the SCCBC was 1.0 wt% or more. On the other hand, when the SCCBC was 10 wt% or more, the adhesive strength started to decrease.
[0143] [Table 2]
[0144] [Test Examples C1 to C6 (Table 3)] Table 3 shows the evaluation results using various thermoplastic resins. LDPE, L-LDPE, and block PP all had strong adhesive properties, with the substrate stretching or breaking before peeling at the adhesive surface.
[0145] [Table 3] [Industrial Applicability]
[0146] The molded articles of the thermoplastic resin composition obtained by the present invention can be used in various applications as the conventional thermoplastic resin compositions having improved physical properties, and are therefore industrially useful. [Explanation of symbols]
[0147] 1, 11, 12 Supply inlets 10, 101 Molding machine 2 Melt mixing section 21 Cylinder 22 Screw 3 Discharge part 4 Pelletizer 5. Container 51 T-die 52 Roller 53 Winding roller 61 Pellets 62 Film
Claims
1. The method for producing a molded article includes melt molding a kneaded resin obtained by kneading a thermoplastic resin and a side-chain crystalline block copolymer, and modifying a surface layer of the molded article, the side chain crystalline block copolymer comprises a first polymer block which is a repeat of a structural unit having an alkyl group having 8 or more carbon atoms in a side chain, and a second polymer block which is a repeat of a structural unit having a functional group; the first polymer block is a polymer of any one monomer (A) selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, the monomer having an alkyl group having 8 or more carbon atoms; the second block is a polymer of any one of monomers (B) selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, the monomer (B) having any one of groups selected from the group consisting of an amino group, an amide group, a sulfo group, an oxyalkylene group, and an oxiranyl group, the thermoplastic resin is one or more resins selected from the group consisting of polyolefin-based resins, polyester-based resins, polystyrene-based resins, and polyacrylic-based resins; The method for producing a molded article, wherein the content of the side-chain crystalline block copolymer in the kneaded resin (mass of side-chain crystalline block copolymer / mass of kneaded resin) is 0.05 to 10.0 mass %.
2. The method for producing a molded article according to claim 1, wherein the functional group is a polar group and / or a functional group having a metal adsorption ability.
3. The composition contains a thermoplastic resin and a side-chain crystalline block copolymer, a surface layer having a portion where the side chain crystalline block copolymer is selectively distributed and arranged; a surface vicinity layer in contact with the surface layer and having a portion containing the side chain crystalline block copolymer, the side chain crystalline block copolymer comprises a first polymer block which is a repeat of a structural unit having an alkyl group having 8 or more carbon atoms in a side chain, and a second polymer block which is a repeat of a structural unit having a functional group; the first polymer block is a polymer of any one monomer (A) selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, the monomer having an alkyl group having 8 or more carbon atoms; the second block is a polymer of any one of monomers (B) selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl ether, vinyl ester, siloxane, α-olefin, and substituted styrene, the monomer (B) having any one of groups selected from the group consisting of an amino group, an amide group, a sulfo group, an oxyalkylene group, and an oxiranyl group, the thermoplastic resin is one or more resins selected from the group consisting of polyolefin-based resins, polyester-based resins, polystyrene-based resins, and polyacrylic-based resins; The content of the side chain crystalline block copolymer is 0.05 to 10.0% by mass.
Citation Information
Patent Citations
Composite container
JP1989045258A
Thermoplastic resin composition and masterbatch containing the composition
JP1999100479A
Thermoplastic resin composition, slidability modifier or improving method for the composition and production of the modifier
JP2000313783A
Modifier for polyolefin-based resin, polyolefin-based composition, and its molded product
JP2001106746A
Thermoplastic resin composition
JP2005112924A